High Degree Multivariate Fuzzy Approximation by Quasi-Interpolation Neural Network Operators - Anastassiou, George A. (Discontinuity, Nonlinearity, and Complexity, 2026)
Here are considered in terms of multivariate fuzzy high approximation to the multivariate unit sequences of multivariate fuzzy quasiinterpolation neural network operators. These operators are multivariate fuzzy analogs of earlier considered multivariate real ones. The derived results generalize earlier real ones into the fuzzy setting. Here the high degree multivariate fuzzy pointwise and uniform convergence with rates to the multivariate fuzzy unit operator are given through multivariate fuzzy inequalities involving the multivariate fuzzy moduli of continuity of the N th order (N ≥ 1) H-fuzzy partial derivatives, of the involved multivariate fuzzy number valued function.